2019
DOI: 10.1002/pmic.201800158
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic and Non‐Malignant Pancreatic Exosome Cargo Reveal Distinct Expression of Oncogenic and Prognostic Factors Involved in Tumor Invasion and Metastasis

Abstract: Exosomes are small extracellular membrane vesicles important in intercellular communication, with their oncogenic cargo attributed to tumor progression and pre‐metastatic niche formation. To gain an insight into key differences in oncogenic composition of exosomes, human non‐malignant epithelial and pancreatic cancer cell models and purified and characterized resultant exosome populations are utilized. Proteomic analysis reveals the selective enrichment of known exosome markers and signaling proteins in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 84 publications
0
57
0
1
Order By: Relevance
“…Moreover, oncogenic exosomes contain factors known to regulate the premetastatic niche (S100A4, F3, ITGβ5, and ANXA1), clinicallyrelevant proteins which correlate with poor prognosis (CLDN1, MUC1) as well as protein networks involved in various cancer hallmarks including proliferation (CLU, CAV1), invasion (PODXL, ITGA3), metastasis (LAMP1, ST14) and immune surveillance escape (B2M). This study highlights the modification of exosome protein content during tumorigenesis and suggests putative components as prognostic and diagnostic biomarkers in pancreatic cancer (46).…”
Section: Ev Proteins As Potential Biomarkers Of Pdacmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, oncogenic exosomes contain factors known to regulate the premetastatic niche (S100A4, F3, ITGβ5, and ANXA1), clinicallyrelevant proteins which correlate with poor prognosis (CLDN1, MUC1) as well as protein networks involved in various cancer hallmarks including proliferation (CLU, CAV1), invasion (PODXL, ITGA3), metastasis (LAMP1, ST14) and immune surveillance escape (B2M). This study highlights the modification of exosome protein content during tumorigenesis and suggests putative components as prognostic and diagnostic biomarkers in pancreatic cancer (46).…”
Section: Ev Proteins As Potential Biomarkers Of Pdacmentioning
confidence: 79%
“…Differences in composition between exosomes from human non-malignant epithelial and pancreatic cancer cells were analyzed by Emmanouilidi et al (46). Proteomic analysis reveals the selective enrichment of known exosome markers and also signaling proteins involved in pancreatic cancer progression (KRAS, CD44, and EGFR) in oncogenic exosomes compared to exosomes from non-malignant cells.…”
Section: Ev Proteins As Potential Biomarkers Of Pdacmentioning
confidence: 99%
“…EEVs may have a high level of pro-angiogenesis molecules, promoting endothelial cell proliferation and the survival and differentiation of fibroblasts into myofibroblasts, leading to tumor vascularization. They can also enhance vessels' permeability, leading to tumor cell diffusion and metastasis [112]. Interest has grown in adipose-derived stem cells in the TME; preclinical studies suggested that adipose-derived stem cells could be a potential tumor promoter, supporting tumor progression and activating several intracellular signals [113].…”
Section: Eevs In Tumor Malignancymentioning
confidence: 99%
“…It has now been widely demonstrated that EVs derived from tumor cells (TEVs) can promote tumor-mediated immune suppression creating a tumor-friendly microenvironment [3,4]. Many studies are specifically focused on small extracellular vesicles (sEVs), to date also named exosomes, a well-characterized subtype of EVs playing a pleiotropic role in different key processes of tumor formation and progression; in fact, EVs are involved in tumor microenvironment (TME) remodeling as angiogenesis [5][6][7], invasion [8,9], metastasis [10][11][12], and resistance to therapies [13,14]. sEVsare nano-sized (40-100 nm) membrane-delimited vesicles that are secreted by almost all cell types under both normal and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%